2011
DOI: 10.1093/ije/dyr011
|View full text |Cite
|
Sign up to set email alerts
|

Explaining low mortality among US immigrants relative to native-born Americans: the role of smoking

Abstract: Low smoking-related mortality was the main reason for immigrants' and Hispanics' longevity advantage in the USA in 2000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
128
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(142 citation statements)
references
References 23 publications
11
128
2
1
Order By: Relevance
“…In Europe this has been documented for England and Wales (Wallace and Kulu 2014), Germany (Razum et al 1998;Ronellenfitsch et al 2006), France (Boulogne et al 2012;Courbage and Khlat 1996), Spain (Moncho et al 2015), and Belgium (Anson 2004), among others. The predominant pattern of lower immigrant all-cause mortality is observed also in high-income countries outside of Europe, such as New Zealand (Hajat et al 2010), Canada (McDonald andKennedy 2004), and the U.S. (Argeseanu, Ruben, and Narayan 2008;Blue and Fenelon 2011;Choi 2012;Singh and Miller 2004;Singh and Siahpush 2002). With the exception of Singh and Miller (2004), the aforementioned studies suggest protective effects of a similar magnitude for male and female immigrants.…”
Section: Existing Researchmentioning
confidence: 97%
See 2 more Smart Citations
“…In Europe this has been documented for England and Wales (Wallace and Kulu 2014), Germany (Razum et al 1998;Ronellenfitsch et al 2006), France (Boulogne et al 2012;Courbage and Khlat 1996), Spain (Moncho et al 2015), and Belgium (Anson 2004), among others. The predominant pattern of lower immigrant all-cause mortality is observed also in high-income countries outside of Europe, such as New Zealand (Hajat et al 2010), Canada (McDonald andKennedy 2004), and the U.S. (Argeseanu, Ruben, and Narayan 2008;Blue and Fenelon 2011;Choi 2012;Singh and Miller 2004;Singh and Siahpush 2002). With the exception of Singh and Miller (2004), the aforementioned studies suggest protective effects of a similar magnitude for male and female immigrants.…”
Section: Existing Researchmentioning
confidence: 97%
“…Many health behaviors that relate to mortality, such as smoking, alcohol use, nutritional intake, and physical activity, have been shown to vary between immigrants and the host population (see e.g., Bennett 1993;Blue and Fenelon 2011;Singh and Siahpush 2002;Wandel 1993). Immigrants may adopt some of the habits of the host population and this may increase or decrease mortality, depending on the prevalence of the behavior in question in the country of origin relative to that in the host population (i.e., whether migrants move from a low risk to a high risk country or vice versa).…”
Section: Acculturation Social Status and Social Causationmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have suggested the role of smoking in differences in mortality between Hispanics and NHWs. 52,[64][65][66][67][68][69] Although studies indicate that foreign-born Hispanics are less likely to smoke than US-born Hispanics, 67,69 none have demonstrated an influence on survival after diagnosis of lung cancer.…”
Section: Patel Et Almentioning
confidence: 99%
“…In our study, there was a paradoxical effect showing a trend toward an improved overall survival in Hispanics compared to Non-Hispanics, even when controlling for all other variables in the multivariate analysis. The Hispanic paradox has been well described (Turra and Elo, 2008;Blue and Fenelon, 2011).…”
Section: Discussionmentioning
confidence: 99%